Hydrological projections of fluvial floods in the Uruguay and Paraná basins under different climate change scenarios - Camilloni, Ines Angela (2013)
Hydrological modeling with climate scenario data is used to develop projections of changes in frequency and duration of flood events in the margins of the lower sections of the Paraná and Uruguay rivers in La Plata Basin for the 21st century. Discharges were simulated with the VIC hydrologic model considering the statistically bias corrected daily maximum and minimum temperatures and rainfall outputs from five regional climate models (RCMs) and different emission scenarios. Results show that although it is expected that compared to current conditions temperature would rise and precipitation would have a slight increase in La Plata Basin during the present century, it could be expected more frequent and lasting fluvial flooding events in the lower Paraná and Uruguay basins. However, the range of results derived from different climate models though consistent in sign, indicate that the uncertainty is large.